Jedediah Kilburn Smith correspondence - Smith, Jedediah Kilburn, 1770-1828.
ALS written by Smith to Jacob Bailey Moore relating to national and New Hampshire politics, especially to the Federal Party, the embargo, and relations with Great Britain.
U.S. representative from New Hampshire and jurist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Moore, Jacob Bailey, -- 1797-1853 -- Correspondence; Federal Party (U.S.); Embargo, 1807-1809.; Great Britain -- Foreign relations -- United States; New Hampshire -- Politics and government -- 1775-1865.; United States -- Foreign relations -- Great Britain; United States -- Politics and government -- 1801-1809.; Jurists; Representatives, U.S. Congress -- New Hampshire